Alternating projection-based iterative learning control for discrete-time systems with non-uniform trial lengths - Zhuang, Zhihe; Tao, Hongfeng; Chen, Yiyang; Rogers, Eric; Oomen, Tom; Paszke, Wojciech (1975- )
This paper develops a novel framework for iterative learning control (ILC) design of discrete-time systems with non-uniform trial lengths by using alternating projections. In contrast to existing works for the non-uniform trial length problem, this paper uses the Hilbert space settings and hence the discrete-time system dynamics with non-uniform trial lengths can be represented by multiple affine subspaces (or linear varieties).
Keywords: iterative learning control; discrete-time systems; alternating projection; non-uniform trial lengths; input constraint